Preparation method and application of hydrotalcite-based metal catalyst
By using hydrotalcite as a support and supporting Mg or Cu and Mg active metals, a highly active and highly selective hydrotalcite-based metal catalyst was prepared, which solved the problems of large particles, easy metal ions agglomeration, and difficult preparation of existing catalysts in N-methylmorpholine synthesis, and achieved efficient N-methylmorpholine synthesis.
Patent Information
- Application Number
- CN202411626995.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
AI Technical Summary
In the synthesis of N-methylmorpholine, existing catalysts have problems such as large particles, easy agglomeration of metal ions, and difficulty in preparation, which limits their application.
Nickel-aluminum binary hydrotalcite was prepared by co-precipitation method and impregnation method, and Mg or Cu and Mg active metals were supported to prepare hydrotalcite-based metal catalysts with high activity and high selectivity.
The prepared catalyst has a large specific surface area, good stability, long life and high activity, and has a high product yield and a high conversion rate of raw material morpholine in the synthesis of N-methylmorpholine.
Smart Images

Figure CN119500093A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a preparation method and application of a hydrotalcite-based metal catalyst. Background Art
[0002] N-methylmorpholine belongs to the heterocyclic tertiary amines with ether structure. It has the dual properties of tertiary amines and ethers and is an important fine chemical raw material and pharmaceutical intermediate. It is widely used in the synthesis of pharmaceutical intermediates such as pesticides, fungicides and plant growth regulators, as well as the synthesis of fine chemical products such as surfactants. It can also be used as an extractant, emulsifier, corrosion inhibitor, polyurethane foam foaming catalyst, etc. There are many ways to synthesize N-methylmorpholine, and there are many synthesis processes depending on the raw materials used. At present, the most common ones are the morpholine method, N-methyldiethanolamine method, diethanolamine method, diethylene glycol method and dichloroethyl ether method.
[0003] Patent CN100548477C discloses a method of co-producing N-methylmorpholine and morpholine using diethylene glycol, liquid ammonia and monomethylamine as raw materials, Ni-Cu / (δ+θ)-Al2O3-MgO, Ni-Cu / (δ+θ)-Al2O3-CaO or Ni-Cu / (δ+θ)-Al2O3-BaO as catalysts, and using a complex reaction process, a large number of catalysts, and difficulty in industrialization. Patent CN104941647B discloses a supported catalyst using N-methyldiethanolamine as raw material, SiO2-Al2O3 complex as carrier, and loaded with iron oxide and nickel oxide active components to react and synthesize N-methylmorpholine. Although the N-methyldiethanolamine method has few by-products and a high yield, the raw materials of the method are expensive and difficult to source, making it difficult to achieve industrial production. Patent CN110773175A discloses using morpholine and methanol as raw materials, using a loaded catalyst having at least two active components in Ni, Cu, Co, Zn and La, Al2O3-TiO2 as a carrier, to prepare N-methylmorpholine by methylation reaction. The reaction can be almost completed quantitatively. According to literature review, the synthetic method of N-methylmorpholine selects the most research on methylation using morpholine as the starting raw material, which is relatively the most promising. However, the catalyst particles used in this method are large, metal ions are easily agglomerated and difficult to prepare, thereby limiting its application. Based on this, it is still necessary to explore a more optimal catalytic system to more efficiently methylate morpholine to obtain N-methylmorpholine. Summary of the invention
[0004] Studies have shown that the template effect of hydrotalcite (LDH) can make various metal ions disperse evenly, so that the catalyst particles are fine, the specific surface area is large, and the catalytic activity is good. In addition, there have been certain studies on the use of hydrotalcite in catalytic N-alkylation reactions, but hydrotalcite has not been used to catalyze the synthesis of N-methylmorpholine by the alcoholamine method.
[0005] The process of the present invention is as follows:
[0006] The N-methylation of morpholine to prepare N-methylmorpholine can also be regarded as the amination process of methanol. The amination mechanism of alcohols has been reported in many literatures: the alcohol is first dehydrated to form the corresponding aldehyde intermediate, and then reacts with amine to form an imine, which is then catalytically hydrogenated. The rate-controlling step of the reaction is the removal of the α hydrogen of the alcohol, and the formation of the imine intermediate does not require a catalyst. Therefore, the catalytic performance required for the amination reaction of alcohols is that the catalyst has the ability to dehydrogenate and hydrogenolyze. Therefore, the selection of the catalyst is the key to whether the reaction can proceed.
[0007] The purpose of the present invention is to design and prepare a catalyst with high activity and high selectivity, synthesize a series of different hydrotalcite-like non-precious metal catalysts, and apply the synthesized catalysts to the synthesis research of N-methylmorpholine. First, Ni is prepared by coprecipitation method. a Al b Binary hydrotalcite, in which Ni a and Al b The ratio of the amount of Ni and Al is expressed as a:b. Then, the active component Mg, or Cu and Mg, is loaded onto Ni by impregnation. a Al b On binary hydrotalcites.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: A hydrotalcite-based metal catalyst, specifically, a nickel-aluminum binary hydrotalcite Ni a Al b -LDH is used as a carrier, loaded with Mg, or loaded with two active metals, Cu and Mg; a:b is (0.5~2):1; the loading amount of Cu is 0~20 wt% (including 0), and the loading amount of Mg is 7~9 wt%; the specific surface area is 162~195 m 2 / g, and the average pore size is 25.1~27.4 nm.
[0009] Preferably, the molar ratio of Cu to Mg in the catalyst is 0-1:1 (including 0).
[0010] Further preferably, the molar ratio of Cu to Mg in the catalyst is 1:1.
[0011] Preferably, the ratio of a:b in the catalyst is 1:1, 0.5:1, 1.5:1 or 2:1.
[0012] Further preferably, the ratio of a:b in the catalyst is 1.5:1.
[0013] The method for preparing the hydrotalcite-based metal catalyst comprises the following steps: (1) Ni(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in deionized water in proportion to prepare a mixed solution, which was recorded as solution A; sodium carbonate was dissolved in deionized water, which was recorded as solution B; solution A and solution B were added to the container at the same rate, and after they were added completely, the pH of the system was adjusted to alkaline; then the mixture was stirred vigorously at room temperature and continued to react at 80-100°C. After the reaction was completed, the mixture was filtered and dried to obtain nickel-aluminum binary hydrotalcite, which was recorded as Ni a Al b -LDH, where a and b are the ratios of Ni and Al; (2) Ni prepared in step (1) a Al b -LDH was added into deionized water, nitrogen was introduced to replace the air in the water, and under nitrogen protection, Mg(NO3)2·6H2O, or Cu(NO3)2·3H2O and Mg(NO3)2·6H2O were added in proportion, and ultrasonic in-situ reduction was carried out at 400 W and 30 °C. After the reaction stopped, the catalyst was centrifuged and dried to obtain a hydrotalcite-based metal catalyst.
[0014] Preferably, in step (1), the concentration of Ni(NO3)2·6H2O in solution A is 0.1-0.4 mol / L.
[0015] Further preferably, in step (1), the concentration of Ni(NO3)2·6H2O in solution A is 0.3 mol / L, and the concentration of Na2CO3 in solution B is 0.5 mol / L.
[0016] More preferably, in step (1), the volume ratio of solution A to solution B is 1-2:1.
[0017] Preferably, in step (1), the pH of the system is adjusted to 9-10 by using sodium hydroxide solution.
[0018] Preferably, in step (1), the mixture is stirred vigorously at room temperature for 5 minutes.
[0019] Preferably, the reaction time in step (1) at 80° C. is 6 h.
[0020] Preferably, after the reaction in step (1) is completed, the mixture is cooled to room temperature, centrifuged and washed until the filtrate is neutral, filtered, and the solid sample is ground into powder and dried in a vacuum drying oven at 60° C. for 12 h.
[0021] Preferably, in step (2), Ni a Al bThe mass volume ratio of -LDH to deionized water was 0.05 g:20 mL.
[0022] The hydrotalcite-based metal catalyst is used in the synthesis of N-methylmorpholine, and the application method is as follows: the hydrotalcite-based metal catalyst is added into a reactor, and the temperature is first increased from room temperature to 190°C at a heating rate of 2.5°C / min, and the pressure is increased to 1.8 MPa, with hydrogen as a carrier gas and a carrier gas flow rate of 100 mL / min; and N-methylmorpholine is synthesized with morpholine and methanol in a molar ratio of 1:20 as reactants.
[0023] Catalyst performance evaluation method: The catalyst was loaded in the reactor. With hydrogen as carrier gas and a carrier gas flow rate of 100 mL / min, the reaction temperature in the fixed bed was first raised to 190 °C, and the heating rate was controlled at 2.5 °C / min. After the temperature of the mixed vaporizer was raised to 190 °C, the centrifugal pump was turned on, and the feed flow and rate of the raw materials were controlled by the shut-off valve and flowmeter according to the required molar ratio to ensure that there was no liquid accumulation in the fixed bed, control the discharge rate, and perform GC analysis on the outlet feed liquid to analyze its composition.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The catalyst prepared by the present invention has a larger specific surface area, providing more active sites for active components.
[0025] 2. The catalyst prepared by the present invention has good stability, long life and high activity.
[0026] 3. The catalyst prepared by the present invention is used for the first time in the synthesis reaction of N-methylmorpholine, and the yield of the product N-methylmorpholine is high and the conversion rate of the raw material morpholine is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Ni in Example 3 1.5 SEM image of Al-LDH; Figure 2 is the Cu-Mg / Ni in Example 3 1.5 SEM image of Al-LDH; Figure 3 Mg / Ni in Example 7 1.5 SEM image of Al-LDH. DETAILED DESCRIPTION
[0028] In order to make the present invention more specific and clear, the present invention is described below in conjunction with embodiments.
[0029] Example 1 A hydrotalcite-based metal catalyst and a preparation method thereof: (1) Preparation of Ni-Al hydrotalcite.
[0030] First, prepare 150 mL of a mixed solution containing Ni(NO3)2·6H2O (0.1 mol / L) and Al(NO3)3·9H2O (0.2 mol / L), which is recorded as solution A. Prepare 100 mL of a solution containing Na2CO3 (0.5 mol / L), which is recorded as solution B. Add solution A and solution B to the three-necked flask at a rate of 20 mL / min, respectively. After the addition is complete, adjust the pH of the mixed solution to 9-10 with sodium hydroxide solution; stir vigorously for 5 min at room temperature. After stirring, place it in an 80 ℃ oil bath and continue stirring for 6 h. Centrifuge the resulting mixed solution and separate the supernatant. Wash the remaining solid with pure water and centrifuge until the pH value of the supernatant is neutral. Then dry it in an oven at 60 ℃ for 12 h to obtain Ni 0.5 Al-LDH.
[0031] (2) Preparation of Cu-Mg / NiAl hydrotalcite catalyst.
[0032] Nitrate solution was used to treat the prepared Ni 0.5 Al-LDH catalyst was loaded by impregnation method. 0.05 gNi 0.5 Al-LDH was added to 20 mL of deionized water, and nitrogen was introduced to replace the air in the aqueous solution. Under nitrogen protection, 20 mL of 0.01 mol / L Cu(NO3)2·3H2O and 20 mL of 0.01 mol / L Mg(NO3)2·6H2O solution were added, and ultrasonic in-situ reduction was performed at 400 W and 30 °C. After the reaction stopped, Ni was centrifuged and dried to obtain 0.5 Al hydrotalcite supported Cu-Mg bimetallic catalyst.
[0033] (3) Catalyst performance evaluation Fill the reactor with 50 g of the prepared Cu-Mg / Ni 0.5 Al-LDH catalyst. The molar ratio of morpholine to methanol is 1:20. With hydrogen as carrier gas and a carrier gas flow rate of 100 mL / min, the reaction temperature in the fixed bed is first raised to 190°C, the heating rate is controlled at 2.5°C / min, and the pressure is raised to 1.8 MPa. After the temperature of the mixed vaporizer is raised to 190°C, methanol is pumped in through a methanol feed pump, the vaporized methanol is mixed with hydrogen, and morpholine is pumped in through a morpholine feed pump. The mixed gas of methanol and hydrogen and the vaporized morpholine enter the reactor, and the reaction produces a crude product. Samples are taken every hour to analyze the content of each component.
[0034] Example 2 A hydrotalcite-based metal catalyst and a preparation method thereof: (1) Preparation of Ni-Al hydrotalcite.
[0035] First, 150 mL of a mixed solution containing Ni(NO3)2·6H2O (0.2 mol / L) and Al(NO3)3·9H2O (0.2 mol / L) was prepared, which was recorded as solution A. 100 mL of a solution containing Na2CO3 (0.5 mol / L) was prepared, which was recorded as solution B. Solution A and solution B were added to a three-necked flask at a rate of 20 mL / min, respectively. After the addition was complete, the pH of the mixed solution was adjusted to 9-10 with sodium hydroxide solution; it was vigorously stirred for 5 min at room temperature. After the stirring was completed, it was placed in an 80 ℃ oil bath and continued to stir for 6 h. The obtained mixed solution was centrifuged to separate the supernatant. The remaining solid was washed with pure water and centrifuged until the pH value of the supernatant was neutral. Then it was dried in an oven at 60 ℃ for 12 h to obtain NiAl-LDH.
[0036] (2) Preparation of Cu-Mg / NiAl hydrotalcite catalyst.
[0037] The prepared NiAl-LDH catalyst was loaded by impregnation method using nitrate solution. 0.05 g NiAl-LDH was added to 20 mL deionized water, nitrogen was introduced to replace the air in the aqueous solution, and 20 mL 0.01 mol / L Cu(NO3)2·3H2O and 20 mL 0.01 mol / L Mg(NO3)2·6H2O solution were added under nitrogen protection, and ultrasonic in-situ reduction was performed at 400 W and 30 °C. After the reaction stopped, the NiAl hydrotalcite-loaded Cu-Mg bimetallic catalyst was obtained by centrifugation and drying.
[0038] (3) Catalyst performance evaluation 50 g of the prepared Cu-Mg / NiAl-LDH catalyst was loaded into the reactor. The molar ratio of morpholine to methanol was 1:20. With hydrogen as carrier gas and a carrier gas flow rate of 100 mL / min, the reaction temperature in the fixed bed was first raised to 190°C, the heating rate was controlled at 2.5°C / min, and the pressure was raised to 1.8 MPa. After the temperature of the mixed vaporizer was raised to 190°C, methanol was pumped in through a methanol feed pump, the vaporized methanol was mixed with hydrogen, and morpholine was pumped in through a morpholine feed pump. The mixed gas of methanol and hydrogen and the vaporized morpholine entered the reactor, and the reaction produced a crude product. Samples were taken every hour for content analysis of each component.
[0039] Example 3 A hydrotalcite-based metal catalyst and a preparation method thereof: (1) Preparation of Ni-Al hydrotalcite.
[0040] First, prepare 150 mL of a mixed solution containing Ni(NO3)2·6H2O (0.3 mol / L) and Al(NO3)3·9H2O (0.2 mol / L), which is recorded as solution A. Prepare 100 mL of a solution containing Na2CO3 (0.5 mol / L), which is recorded as solution B. Add solution A and solution B to a three-necked flask at a rate of 20 mL / min, respectively. After the addition is complete, adjust the pH of the mixed solution to 9-10 with sodium hydroxide solution; stir vigorously for 5 min at room temperature. After stirring, place it in an 80 ℃ oil bath and continue stirring for 6 h. Centrifuge the resulting mixed solution and separate the supernatant. Wash the remaining solid with pure water and centrifuge until the pH value of the supernatant is neutral. Then dry it in an oven at 60 ℃ for 12 h to obtain Ni 1.5 The microstructure of Al-LDH is shown in the figure Figure 1 shown.
[0041] (2) Preparation of Cu-Mg / NiAl hydrotalcite catalyst.
[0042] Nitrate solution was used to treat the prepared Ni 1.5 Al-LDH catalyst was loaded by impregnation method. 0.05 gNi 1.5 Al-LDH was added to 20 mL of deionized water, and nitrogen was introduced to replace the air in the aqueous solution. Under nitrogen protection, 20 mL of 0.01 mol / L Cu(NO3)2·3H2O and 20 mL of 0.01 mol / L Mg(NO3)2·6H2O solution were added, and ultrasonic in-situ reduction was performed at 400 W and 30 °C. After the reaction stopped, Ni was centrifuged and dried to obtain 1.5 The microstructure of Al hydrotalcite-supported Cu-Mg bimetallic catalyst is shown in the figure Figure 2 shown.
[0043] (3) Catalyst performance evaluation Fill the reactor with 50 g of the prepared Cu-Mg / Ni 1.5 Al-LDH catalyst. The molar ratio of morpholine to methanol is 1:20. With hydrogen as carrier gas and a carrier gas flow rate of 100 mL / min, the reaction temperature in the fixed bed is first raised to 190°C, the heating rate is controlled at 2.5°C / min, and the pressure is raised to 1.8 MPa. After the temperature of the mixed vaporizer is raised to 190°C, methanol is pumped in through a methanol feed pump, the vaporized methanol is mixed with hydrogen, and morpholine is pumped in through a morpholine feed pump. The mixed gas of methanol and hydrogen and the vaporized morpholine enter the reactor, and the reaction produces a crude product. Samples are taken every hour to analyze the content of each component.
[0044] Example 4 A hydrotalcite-based metal catalyst and a preparation method thereof: (1) Preparation of Ni-Al hydrotalcite.
[0045] First, 150 mL of a mixed solution containing Ni(NO3)2·6H2O (0.4 mol / L) and Al(NO3)3·9H2O (0.2 mol / L) was prepared, which was recorded as solution A. 100 mL of a solution containing Na2CO3 (0.5 mol / L) was prepared, which was recorded as solution B. Solution A and solution B were added to a three-necked flask at a rate of 20 mL / min, respectively. After the addition was complete, the pH of the mixed solution was adjusted to 9-10 with sodium hydroxide solution; it was vigorously stirred for 5 min at room temperature. After the stirring was completed, it was placed in an 80 ℃ oil bath and continued to stir for 6 h. The obtained mixed solution was centrifuged to separate the supernatant. The remaining solid was washed with pure water and centrifuged until the pH value of the supernatant was neutral. Then it was dried in an oven at 60 ℃ for 12 h to obtain Ni2Al-LDH.
[0046] (2) Preparation of Cu-Mg / NiAl hydrotalcite catalyst.
[0047] The prepared Ni2Al-LDH catalyst was loaded by impregnation method using nitrate solution. 0.05 g Ni2Al-LDH was added to 20 mL deionized water, nitrogen was introduced to replace the air in the aqueous solution, and 20 mL 0.01 mol / L Cu(NO3)2·3H2O and 20 mL 0.01 mol / L Mg(NO3)2·6H2O solution were added under nitrogen protection, and ultrasonic in-situ reduction was performed at 400 W and 30 °C. After the reaction stopped, the Ni2Al hydrotalcite-loaded Cu-Mg bimetallic catalyst was obtained by centrifugation and drying.
[0048] (3) Catalyst performance evaluation 50 g of the prepared Cu-Mg / Ni2Al-LDH catalyst was loaded into the reactor. The molar ratio of morpholine to methanol was 1:20. With hydrogen as carrier gas and a carrier gas flow rate of 100 mL / min, the reaction temperature in the fixed bed was first raised to 190°C, the heating rate was controlled at 2.5°C / min, and the pressure was raised to 1.8 MPa. After the temperature of the mixed vaporizer was raised to 190°C, methanol was pumped in through a methanol feed pump, the vaporized methanol was mixed with hydrogen, and morpholine was pumped in through a morpholine feed pump. The mixed gas of methanol and hydrogen and the vaporized morpholine entered the reactor, and the reaction produced a crude product. Samples were taken every hour for content analysis of each component.
[0049] Example 5 A hydrotalcite-based metal catalyst and a preparation method thereof: (1) Preparation of Ni-Al hydrotalcite.
[0050] First, prepare 150 mL of a mixed solution containing Ni(NO3)2·6H2O (0.1 mol / L) and Al(NO3)3·9H2O (0.2 mol / L), which is recorded as solution A. Prepare 100 mL of a solution containing Na2CO3 (0.5 mol / L), which is recorded as solution B. Add solution A and solution B to the three-necked flask at a rate of 20 mL / min, respectively. After the addition is complete, adjust the pH of the mixed solution to 9-10 with sodium hydroxide solution; stir vigorously at room temperature for 5 min. After stirring, place it in an 80 ℃ oil bath and continue stirring for 6 h. Centrifuge the resulting mixed solution and separate the supernatant. Wash the remaining solid with pure water and centrifuge until the pH value of the supernatant is neutral. Then dry it in an oven at 60 ℃ for 12 h to obtain Ni 0.5 Al-LDH.
[0051] (2) Preparation of Mg / NiAl-type hydrotalcite catalysts.
[0052] Nitrate solution was used to treat the prepared Ni 0.5 Al-LDH catalyst was loaded by impregnation method. 0.05 gNi 0.5 Al-LDH was added to 20 mL of deionized water, nitrogen was introduced to replace the air in the aqueous solution, and 20 mL of 0.01 mol / L Mg(NO3)2·6H2O solution was added under nitrogen protection. Ultrasonic in-situ reduction was performed at 400 W and 30 °C. After the reaction stopped, Ni was centrifuged and dried to obtain 0.5 Al hydrotalcite supported Mg metal catalyst.
[0053] (3) Catalyst performance evaluation Fill the reactor with 50 g of prepared Mg / Ni 0.5 Al-LDH catalyst. The molar ratio of morpholine to methanol is 1:20. With hydrogen as carrier gas and a carrier gas flow rate of 100 mL / min, the reaction temperature in the fixed bed is first raised to 190°C, the heating rate is controlled at 2.5°C / min, and the pressure is raised to 1.8 MPa. After the temperature of the mixed vaporizer is raised to 190°C, methanol is pumped in through a methanol feed pump, the vaporized methanol is mixed with hydrogen, and morpholine is pumped in through a morpholine feed pump. The mixed gas of methanol and hydrogen and the vaporized morpholine enter the reactor, and the reaction produces a crude product. Samples are taken every hour to analyze the content of each component.
[0054] Example 6 A hydrotalcite-based metal catalyst and a preparation method thereof: (1) Preparation of Ni-Al hydrotalcite.
[0055] First, 150 mL of a mixed solution containing Ni(NO3)2·6H2O (0.2 mol / L) and Al(NO3)3·9H2O (0.2 mol / L) was prepared, which was recorded as solution A. 100 mL of a solution containing Na2CO3 (0.5 mol / L) was prepared, which was recorded as solution B. Solution A and solution B were added to a three-necked flask at a rate of 20 mL / min, respectively. After the addition was complete, the pH of the mixed solution was adjusted to 9-10 with sodium hydroxide solution; it was vigorously stirred for 5 min at room temperature. After the stirring was completed, it was placed in an 80 ℃ oil bath and continued to stir for 6 h. The obtained mixed solution was centrifuged to separate the supernatant. The remaining solid was washed with pure water and centrifuged until the pH value of the supernatant was neutral. Then it was dried in an oven at 60 ℃ for 12 h to obtain NiAl-LDH.
[0056] (2) Preparation of Mg / NiAl-type hydrotalcite catalysts.
[0057] The prepared NiAl-LDH catalyst was loaded by impregnation method using nitrate solution. 0.05 g NiAl-LDH was added to 20 mL deionized water, nitrogen was introduced to replace the air in the aqueous solution, and 20 mL 0.01 mol / L Mg(NO3)2·6H2O solution was added under nitrogen protection, and ultrasonic in-situ reduction was performed at 400 W and 30 °C. After the reaction stopped, the NiAl hydrotalcite-loaded Mg metal catalyst was obtained by centrifugation and drying.
[0058] (3) Catalyst performance evaluation 50 g of the prepared Mg / NiAl-LDH catalyst was loaded into the reactor. The molar ratio of morpholine to methanol was 1:20. With hydrogen as carrier gas and a carrier gas flow rate of 100 mL / min, the reaction temperature in the fixed bed was first raised to 190 °C, the heating rate was controlled at 2.5 °C / min, and the pressure was raised to 1.8 MPa. After the temperature of the mixed vaporizer was raised to 190 °C, methanol was pumped in through a methanol feed pump, the vaporized methanol was mixed with hydrogen, and morpholine was pumped in through a morpholine feed pump. The mixed gas of methanol and hydrogen and the vaporized morpholine entered the reactor, and the reaction produced a crude product. Samples were taken every hour for content analysis of each component.
[0059] Example 7 A hydrotalcite-based metal catalyst and a preparation method thereof: (1) Preparation of Ni-Al hydrotalcite.
[0060] First, prepare 150 mL of a mixed solution containing Ni(NO3)2·6H2O (0.3 mol / L) and Al(NO3)3·9H2O (0.2 mol / L), which is recorded as solution A. Prepare 100 mL of a solution containing Na2CO3 (0.5 mol / L), which is recorded as solution B. Add solution A and solution B to a three-necked flask at a rate of 20 mL / min, respectively. After the addition is complete, adjust the pH of the mixed solution to 9-10 with sodium hydroxide solution; stir vigorously for 5 min at room temperature. After stirring, place it in an 80 ℃ oil bath and continue stirring for 6 h. Centrifuge the resulting mixed solution and separate the supernatant. Wash the remaining solid with pure water and centrifuge until the pH value of the supernatant is neutral. Then dry it in an oven at 60 ℃ for 12 h to obtain Ni 1.5 Al-LDH.
[0061] (2) Preparation of Mg / NiAl-type hydrotalcite catalysts.
[0062] Nitrate solution was used to treat the prepared Ni 1.5 Al-LDH catalyst was loaded by impregnation method. 0.05 gNi 1.5 Al-LDH was added to 20 mL of deionized water, nitrogen was introduced to replace the air in the aqueous solution, and 20 mL of 0.01 mol / L Mg(NO3)2·6H2O solution was added under nitrogen protection. Ultrasonic in-situ reduction was performed at 400 W and 30 °C. After the reaction stopped, Ni was centrifuged and dried to obtain 1.5 The microstructure of Al hydrotalcite-supported Mg metal catalyst is shown in the figure Figure 3 shown.
[0063] (3) Catalyst performance evaluation Fill the reactor with 50 g of prepared Mg / Ni 1.5 Al-LDH catalyst. The molar ratio of morpholine to methanol is 1:20. With hydrogen as carrier gas and a carrier gas flow rate of 100 mL / min, the reaction temperature in the fixed bed is first raised to 190°C, the heating rate is controlled at 2.5°C / min, and the pressure is raised to 1.8 MPa. After the temperature of the mixed vaporizer is raised to 190°C, methanol is pumped in through a methanol feed pump, the vaporized methanol is mixed with hydrogen, and morpholine is pumped in through a morpholine feed pump. The mixed gas of methanol and hydrogen and the vaporized morpholine enter the reactor, and the reaction produces a crude product. Samples are taken every hour to analyze the content of each component.
[0064] Example 8 A hydrotalcite-based metal catalyst and a preparation method thereof: (1) Preparation of Ni-Al hydrotalcite.
[0065] First, 150 mL of a mixed solution containing Ni(NO3)2·6H2O (0.4 mol / L) and Al(NO3)3·9H2O (0.2 mol / L) was prepared, which was recorded as solution A. 100 mL of a solution containing Na2CO3 (0.5 mol / L) was prepared, which was recorded as solution B. Solution A and solution B were added to a three-necked flask at a rate of 20 mL / min, respectively. After the addition was complete, the pH of the mixed solution was adjusted to 9-10 with sodium hydroxide solution; it was vigorously stirred for 5 min at room temperature. After the stirring was completed, it was placed in an 80 ℃ oil bath and continued to stir for 6 h. The obtained mixed solution was centrifuged to separate the supernatant. The remaining solid was washed with pure water and centrifuged until the pH value of the supernatant was neutral. Then it was dried in an oven at 60 ℃ for 12 h to obtain Ni2Al-LDH.
[0066] (2) Preparation of Mg / NiAl-type hydrotalcite catalysts.
[0067] The prepared Ni2Al-LDH catalyst was loaded by impregnation method using nitrate solution. 0.05 g Ni2Al-LDH was added to 20 mL deionized water, nitrogen was introduced to replace the air in the aqueous solution, and 20 mL 0.01 mol / L Mg(NO3)2·6H2O solution was added under nitrogen protection, and ultrasonic in-situ reduction was performed at 400 W and 30 °C. After the reaction stopped, the Ni2Al hydrotalcite-loaded Mg metal catalyst was obtained by centrifugation and drying.
[0068] (3) Catalyst performance evaluation 50 g of the prepared Mg / Ni2Al-LDH catalyst was loaded into the reactor. The molar ratio of morpholine to methanol was 1:20. With hydrogen as carrier gas and a carrier gas flow rate of 100 mL / min, the reaction temperature in the fixed bed was first raised to 190°C, the heating rate was controlled at 2.5°C / min, and the pressure was raised to 1.8 MPa. After the temperature of the mixed vaporizer was raised to 190°C, methanol was pumped in through a methanol feed pump, the vaporized methanol was mixed with hydrogen, and morpholine was pumped in through a morpholine feed pump. The mixed gas of methanol and hydrogen and the vaporized morpholine entered the reactor, and the reaction produced a crude product. Samples were taken every hour for content analysis of each component.
[0069] Comparative Example 1 The concentration of Ni(NO3)2·6H2O in the catalyst carrier was replaced with 1.0 mol / L, and the rest was the same as in Example 1.
[0070] Comparative Example 2 The concentration of Mg(NO3)2·6H2O in the catalyst active component was replaced with 0.02 mol / L, and the rest was the same as in Example 1.
[0071] Comparative Example 3 The catalyst carrier was replaced with purchased γ-Al2O3 (Sinopharm Chemical Reagent Co., Ltd., analytical grade), and the rest was the same as in Example 1.
[0072] The specific parameters of the catalysts prepared by the methods described in Examples 1-8 and Comparative Examples 1-3 are shown in Table 1.
[0073] The catalysts prepared by the methods described in Examples 1-8 and Comparative Examples 1-3 were used to catalyze the preparation of N-methylmorpholine. The results are shown in Table 2.
[0074] Table 1 Specific parameters of catalysts in Examples and Comparative Examples
[0075] From the specific surface area data of the catalyst in Table 1, it is found that in the examples, as the Ni content increases, the specific surface area of the catalyst increases, but when the content increases again, the specific surface area decreases. After the introduction of Cu, both the specific surface area and the pore size increase, which may be due to the introduction of Cu, which gradually reduces the average distance between metal ions and increases the interlayer spacing, resulting in an increase in the specific surface area.
[0076] Table 2 Experimental results of using the catalysts of the examples and comparative examples for the synthesis of N-methylmorpholine
[0077] According to the experimental result of Table 2 embodiment, it can be seen that along with the increase of Ni content, the transformation efficiency of raw material morpholine increases, and the yield of N-methylmorpholine also obviously improves, but along with the increase of Ni content, productive rate can reduce on the contrary, and this is that Ni adds the hydrogenolysis ability of catalyst.The loaded catalyst containing Mg and Cu obviously improves morpholine transformation efficiency and N-methylmorpholine yield than the loaded catalyst containing only Mg in catalytic process, and Mg and Cu strengthen the catalytic activity of catalyst.Compared with Comparative Example, embodiment group has higher morpholine transformation efficiency, and N-methylmorpholine productive rate is higher.
Claims
1. A hydrotalcite-based metal catalyst, characterized in that: Nickel-aluminum binary hydrotalcite Ni a Al b -LDH is a carrier loaded with Mg, or loaded with two active metals Cu and Mg; a:b is (0.5~2):1; the loading amount of Cu is 0~20 wt% (including 0), the loading amount of Mg is 7~9 wt%; the specific surface area is 162~195 m 2 / g, and the average pore size is 25.1~27.4nm.
2. A hydrotalcite-based metal catalyst according to claim 1, characterized in that: The molar ratio of Cu to Mg in the catalyst is 0-1:1 (including 0).
3. A hydrotalcite-based metal catalyst according to claim 2, characterized in that: The molar ratio of Cu to Mg in the catalyst is 1:
1.
4. A hydrotalcite-based metal catalyst according to claim 1, characterized in that: The ratio of a:b in the catalyst is 1:1, 0.5:1, 1.5:1 or 2:1; preferably, the ratio of a:b in the catalyst is 1.5:
1.
5. The method for preparing a hydrotalcite-based metal catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Ni(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in deionized water in proportion to prepare a mixed solution, which was recorded as solution A; sodium carbonate was dissolved in deionized water, which was recorded as solution B; solution A and solution B were added to the container at the same rate, and after they were added completely, the pH of the system was adjusted to alkaline; then the mixture was stirred vigorously at room temperature and continued to react at 80-100°C. After the reaction was completed, the mixture was filtered and dried to obtain nickel-aluminum binary hydrotalcite, which was recorded as Ni a Al b -LDH, where a and b are the ratios of Ni and Al; (2) Ni prepared in step (1) a Al b -LDH is added to deionized water, nitrogen is introduced to replace the air in the water, and under nitrogen protection, Mg(NO3)2·6H2O, or Cu(NO3)2·3H2O and Mg(NO3)2·6H2O are added in proportion, and ultrasonic in-situ reduction is carried out at 400 W and 30°C. After the reaction stops, centrifugal separation and drying are carried out to obtain a hydrotalcite-based metal catalyst.
6. The method for preparing a hydrotalcite-based metal catalyst according to claim 5, characterized in that: In step (1), the concentration of Ni(NO3)2·6H2O in solution A is 0.1-0.4 mol / L; preferably, in step (1), the concentration of Ni(NO3)2·6H2O in solution A is 0.3 mol / L, and the concentration of Na2CO3 in solution B is 0.5 mol / L; further preferably, in step (1), the volume ratio of solution A to solution B is 1-2:
1.
7. The method for preparing a hydrotalcite-based metal catalyst according to claim 6, characterized in that: In step (1), the pH of the system is adjusted to 9-10 by sodium hydroxide solution; preferably, in step (1), the mixture is vigorously stirred for 5 minutes at room temperature; preferably, in step (1), the reaction time at 80° C. is 6 hours.
8. The method for preparing a hydrotalcite-based metal catalyst according to claim 6, characterized in that: After the reaction in step (1) is completed, the mixture is cooled to room temperature, centrifuged and washed until the filtrate is neutral, filtered, and the solid sample is ground into powder and dried in a vacuum drying oven at 60°C for 12 h.
9. The method for preparing a hydrotalcite-based metal catalyst according to claim 6, characterized in that: Step (2) Ni a Al b The mass volume ratio of -LDH to deionized water was 0.05 g:20 mL.
10. Use of the hydrotalcite-based metal catalyst according to any one of claims 1 to 4 in the synthesis of N-methylmorpholine, characterized in that: The application method is as follows: the hydrotalcite-based metal catalyst is added into a reactor, and the temperature is first increased from room temperature to 190°C at a heating rate of 2.5°C / min, and the pressure is increased to 1.8 MPa, with hydrogen as a carrier gas and a carrier gas flow rate of 100 mL / min; morpholine and methanol in a molar ratio of 1:20 are used as reactants to synthesize N-methylmorpholine.
Citation Information
Patent Citations
Catalyst required for coproducing N-methyl morpholine and morpholine
CN100548477C
Methods for synthesizing N-methylmorpholine and the supported catalysts used
CN104941647B
Supported metal catalyst, preparation method and application thereof, and synthesis process of N-methylmorpholine
CN110773175A